2018
DOI: 10.4049/jimmunol.1701075
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Isoform of FASTK Modulates Nonopsonic Phagocytosis of Bacteria by Macrophages via Regulation of Respiratory Complex I

Abstract: full#ref-list-1 , 16 of which you can access for free at: cites 47 articles This article average * 4 weeks from acceptance to publication Fast Publication! • Every submission reviewed by practicing scientists No Triage! • from submission to initial decision Rapid Reviews! 30 days* • Submit online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…FASTK is recently identified as a RNA-binding protein to promote MTND6 mRNA maturation (Jourdain et al, 2015). Genetic ablation of FASTK causes a marked reduction of complex I activity in mammalian cells, highlighting FASTK is essential to maintain normal complex I function (García Del Río et al, 2018;Gomez-Niño et al, 2018). The present study shows that the FASTK deficient heart is highly susceptible to I/R-induced complex I dysfunction and respiration, confirming that FASTK critically modulates myocardial mitochondrial complex I activity even under stressful conditions such as I/R.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…FASTK is recently identified as a RNA-binding protein to promote MTND6 mRNA maturation (Jourdain et al, 2015). Genetic ablation of FASTK causes a marked reduction of complex I activity in mammalian cells, highlighting FASTK is essential to maintain normal complex I function (García Del Río et al, 2018;Gomez-Niño et al, 2018). The present study shows that the FASTK deficient heart is highly susceptible to I/R-induced complex I dysfunction and respiration, confirming that FASTK critically modulates myocardial mitochondrial complex I activity even under stressful conditions such as I/R.…”
Section: Discussionsupporting
confidence: 73%
“…In mammalian cells, FASTK specifically interacts with the mRNA of NADH dehydrogenase subunit 6 (MTND6, a mitochondrial gene encoding a subunit of complex I) at various sites and is essential for the processing and maturation of MTND6 mRNA (Jourdain et al, 2015). In vivo and in vitro studies have confirmed that genetic ablation of FASTK decreased the expression of MTND6 and thereafter suppressed mitochondrial complex I activity approximately by 50% (García Del Río et al, 2018;Gomez-Niño et al, 2018). These data reveal that FASTK is a novel and important modulator of mitochondrial complex I activity and respiratory function.…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytosis of macrophages is also regulated by Fas 48. Fas-activated serine/threonine kinase (FASTK) negatively regulates phagocytosis of bacteria by macrophages 49. Although FAS induced by ENVs is involved in cell apoptosis, our data suggest that ENVs do not induce apoptosis of macrophages which can be explained by the reduction of CD36, another apoptosis-related protein 50.…”
Section: Discussionmentioning
confidence: 74%
“…The KCNN4 gene is functionally operational, being present in synovial fibroblasts associated with RA, and plays a role in controlling cell growth and the secretion of harmful and pro-inflammatory substances 50 . NDUFS3, a pro-oxidant component of electron transport chain (ETC) complex I, regulates nonopsonic phagocytosis of bacteria in macrophages 51 . Although the exact cause of NDUFS3 in RA remains uncertain, certain research has indicated its role in the progression of various conditions, including systemic lupus erythematosus (SLE) and lung adenocarcinoma (LUAD) 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%